Engineered Panax notoginseng polysaccharide micelles inhibit macrophage polarization and delay the progression of rheumatoid arthritis via JAK2-STAT3 signaling pathway - Yang Yu; Liang Kong; Rui-bo Guo; Ya-ni Zhang; Shu-tong Li; Feng-yuan Zhang; Xin Wang; Yang Liu; Xiu-Ying Li; Xue-tao Li (Journal of Nanobiotechnology)
Abstract Background The imbalance of macrophage polarization plays a pivotal role in the progression of rheumatoid arthritis (RA). Reprogramming macrophages from the pro-inflammatory M1 phenotype to the anti-inflammatory M2 phenotype is considered a promising therapeutic strategy. Methods To address this challenge, Panax notoginseng polysaccharides (PNP) with varying molecular weights were chemically conjugated with deoxycholic acid (DC) to obtain amphiphilic conjugates (PNP-DC), which self-assembled into micelles (PNP-Ms). After screening for optimal molecular weight, folic acid (FA) was introduced onto the micelle surface, and Polyphyllin I (PPI) was encapsulated to form FA-modified, PPI-loaded micelles (FA-PPI-Ms) with macrophage-targeting capability. Results FA-PPI-Ms showed enhanced cellular uptake via FA receptor–mediated endocytosis and effectively eliminated reactive oxygen species (ROS), reduced inflammatory cytokine production, and exhibited good biosafety. In vivo, FA-PPI-Ms significantly alleviated joint swelling and inflammation in RA rat models. Mechanistic studies based on RNA sequencing and experimental validation revealed that FA-PPI-Ms suppressed the JAK2/STAT3 signaling pathway, thereby promoting M2 macrophage polarization and restoring the M1/M2 balance. Conclusion This study presents a novel FA-PPI-Ms delivery system for targeted macrophages. By modulating polarization through inhibition of JAK2/STAT3 signaling, the system offers a promising therapeutic strategy for RA and potentially other inflammatory diseases.